Navigating Argumentation - Furkan Yazici (Informal Logic)
Abstract: Michael Gilbert challenges established norms in argumentation theory by introducing a multi-modal framework that incorporates emotive, visceral, and kisceral dimensions alongside logical modes in constructing arguments. This article critically assesses Gilbert’s multi-modal argument framework, highlighting his departure from the rational structure of arguments. Gilbert proposes distinct evaluation criteria for different argument forms, a deviation from traditional rational frameworks. To address this discrepancy within Gilbert’s framework, this paper advocates a middle ground. This position aims to appreciate extra-logical elements present in arguments while maintaining fidelity to logical structures. Bertrand Russell’s notion of knowledge by acquaintance is utilized to construct this intermediary standpoint.